Sodium Nitrate Passivation as a Novel Insulation Technology for Soft Magnetic Composites. (January 2023) - Yan, Mi; Chen, Qiming; Liu, Dong; Wu, Chen; Wang, Jian
Abstract: Sodium nitrate passivation has been developed as a new insulation technology for the production of FeSiAl soft magnetic composites (SMCs). In this work, the evolution of coating layers grown at different pH values is investigated involving analyses on their composition and microstructure. An insulation coating obtained using an acidic NaNO3 solution is found to contain Fe2 O3, SiO2, Al2 O3, and AlO(OH). The Fe2 O3 transforms into Fe3 O4 with weakened oxidizability of the NO3 – at an elevated pH, whereas an alkaline NaNO3 solution leads to the production of Al2 O3, AlO(OH), and SiO2 . Such growth is explained from both thermodynamic and kinetic perspectives and is correlated to the soft magnetic properties of the FeSiAl SMCs. Under tuned passivation conditions, optimal performance with an effective permeability of 97.2 and a core loss of 296.4 mW∙cm −3 is achieved at 50 kHz and 100 mT.